1961
DOI: 10.1149/1.2428235
|View full text |Cite
|
Sign up to set email alerts
|

Some Observations of Copper Deposits on Single Crystals of Copper

Abstract: Isolated faces of copper single crystals were plated with copper from copper sulfate‐sulfuric acid solutions. Deposits on {100} and {110} faces, despite the presence of grain boundaries, gave x‐ray diffraction patterns showing uniform lattice orientation. The grain boundaries were associated with topographic features of the deposits. Over‐all metal distribution showed a tendency to deviate from that of poly crystal deposits on polycrystalline bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1963
1963
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These are (a) the theoretical ~ is greater than the experimental T to the extent of 1-2 orders of magnitude (agreement being obtained only when 5 ----10 -3 cm for unstirred solutions), and (b) zinc deposition during the initiation time T has been shown (24) to produce roughening of the electrode surface without any increase in the total current; such microsurface roughening, according to the former model (20) above, should have led to an exponential i --t relationship. 7 Thus, it would appear that these discrepancies, along with the observation that the total current does not increase appreciably until the dendrite length approaches the value of 5 (section above on Summary of the phenonemology), indicate that the i --t phenomenon is due to processes following initiation.…”
Section: Total Current-time Phenomenon--the Increase Inmentioning
confidence: 99%
See 1 more Smart Citation
“…These are (a) the theoretical ~ is greater than the experimental T to the extent of 1-2 orders of magnitude (agreement being obtained only when 5 ----10 -3 cm for unstirred solutions), and (b) zinc deposition during the initiation time T has been shown (24) to produce roughening of the electrode surface without any increase in the total current; such microsurface roughening, according to the former model (20) above, should have led to an exponential i --t relationship. 7 Thus, it would appear that these discrepancies, along with the observation that the total current does not increase appreciably until the dendrite length approaches the value of 5 (section above on Summary of the phenonemology), indicate that the i --t phenomenon is due to processes following initiation.…”
Section: Total Current-time Phenomenon--the Increase Inmentioning
confidence: 99%
“…Reddy (4) has suggested that the critical overpotential may be related to the stacking fault energy of the crystal lattice (5,6) necessary for the formation of a twin plane, through which it was proposed that the dendrite propagated. The existence of twin planes in dendrites has been reported on numerous occasions (7)(8)(9), whereas evidence for the single crystal nature of dendrites (10) has also been reported. It has yet to be shown that twin planes play a necessary part in dendrite initiation and propagation (11,12).…”
mentioning
confidence: 99%
“…p << n and thus n ~ n ~ ~ po) Eq. [1] may be written for the interstitial case as J ------Did (p + n)/dx + epoE/(kT) -k P~ ~1/(kT) ] [7] Differential forms of Eq. [6] and [7] may be combined with Poisson's equation (i.e., dE/dx = --ep/eeo) to give…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Denoting the two ions by subscripts 1 and 2, two parallel flux equations may be written following Eq. [7]. We assume that the ions exhibit separate partial molar volumes, interstitial diffusion coefficients and energies of defect formation and that the conditions for local equilibrium discussed previously hold independently for each ion.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Epitaxial growth of copper single crystals by electrodeposition is very well documented, particularly from sulfate solutions (1)(2)(3)(4)(5)(6)(7)(8). Not so well known, however, is the degree of perfection which can be attained by electrodeposition, as well as the characteristics of the defect structure.…”
mentioning
confidence: 99%